Seven Decades of Solving Roma-related Security Challenges in Pomurje - Eman, Katja; Car, Saša; Ivančić, Damir; Bagari, Dejan (10. Nacionalna konferenca o varnosti v lokalnih skupnostih: Mirna, varna in inkluzivna družba ter varnost v lokalnih skupnostih, 2024)
In July 1952, a paper was published in the journal Kriminalistična služba, (now called Journal of Criminal Investigation and Criminology), entitled “Gypsy burglary gang in Prekmurje warned about the gypsy problem in Slovenia”. We believe that the police and the wider local community involved in solving the described case present one of the important milestones in solving Roma-related problems in this part of Slovenia. This paper presents a chronological overview of important events in solving Roma-related problems from the police and social work point of view. When it comes to problems (co-creating solutions) in local communities, including Roma, mutual (inter-institutional) cooperation and information sharing and support are important for joint response to individual and sometimes crisis situations. The cooperation between the police, social services, and the Roma minority in Pomurje is at a high level and can be an example of good practice for other regions.